2008
DOI: 10.1016/j.jhydrol.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of potential aquifer recharge: Application to the Basin of Mexico

Abstract: Regional estimates of aquifer recharge are needed in data-scarce regions such as the Basin of Mexico, where nearly 20 million people are located and where the Basin's aquifer system represents the main water source. In order to develop the spatio-temporal estimates of aquifer recharge and to analyze to what extent urban growth has affected aquifer recharge, this work presents a daily soil water balance which uses different vegetation and soil types as well as the effect of topography on climatological variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Consistent with Burns et al [69], Carrera-Hernández and Gaskin [27] find that the major portion of the basin's recharge flow occurs in the Sierra Nevada, Chichinautzin and Sierra de Guadalupe. Similar conclusions are found in the studies by Ortega and Farvolden [70] and in Angeles-Serrano [26].…”
Section: The Aquifer System Of Central Mexicosupporting
confidence: 82%
See 4 more Smart Citations
“…Consistent with Burns et al [69], Carrera-Hernández and Gaskin [27] find that the major portion of the basin's recharge flow occurs in the Sierra Nevada, Chichinautzin and Sierra de Guadalupe. Similar conclusions are found in the studies by Ortega and Farvolden [70] and in Angeles-Serrano [26].…”
Section: The Aquifer System Of Central Mexicosupporting
confidence: 82%
“…Carrera-Hernández and Gaskin [27] suggest that the basin's geology has protected the aquifer system from pollution (due to the impermeable clay layer below Mexico City, a conclusion also reached by Edmunds et al [73] and by Bojórquez et al [71]), and as shown by urbanization (due to the differentiated slopes of the mountain range). However, these conclusions are to be taken cautiously: Carrera-Hernández and Gaskin calibrated their data for the period between 1971 and 1981, when the urban sprawl still did not invade the forested areas, as it has done afterwards.…”
Section: The Aquifer System Of Central Mexicomentioning
confidence: 76%
See 3 more Smart Citations